2018
DOI: 10.1093/nop/npy053
|View full text |Cite
|
Sign up to set email alerts
|

Hypofractionated stereotactic radiotherapy for intracranial meningioma: a systematic review

Abstract: Background The availability of image guidance and intensity modulation has led to the increasing use of hypofractionated stereotactic radiotherapy (hSRT) as an alternative to conventionally fractionated radiotherapy or radiosurgery for intracranial meningiomas (ICMs). As the safety and efficacy of this approach is not well characterized, we conducted a systematic review of the literature to assess the clinical outcomes of hSRT in the setting of ICMs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…So far, several studies focused on a hypofractionated approach have been published with good results and low toxicity rate [8-14, 30, 31]. Nevertheless, safety and efficacy of this approach is not well characterized and the reported follow-up is too short for drawing any definitive conclusion [34].…”
Section: Discussionmentioning
confidence: 99%
“…So far, several studies focused on a hypofractionated approach have been published with good results and low toxicity rate [8-14, 30, 31]. Nevertheless, safety and efficacy of this approach is not well characterized and the reported follow-up is too short for drawing any definitive conclusion [34].…”
Section: Discussionmentioning
confidence: 99%
“…There are limited prior reports on the use of hypofractionated RT for meningioma, though none have focused exclusively on the elderly subgroup and most had evaluated 5-fraction regimens. Nguyen et al performed a systematic review of hypofractionated stereotactic radiotherapy and found low rates of late toxicity and high grades of crude local control [ 9 ]. Radiologic response was reported; 96% of tumors treated remained stable or decreased in size, while an increase in size occurred in 4%.…”
Section: Discussionmentioning
confidence: 99%
“…However, neurosurgical intervention or fractionated radiation treatment (up to six weeks) can be challenging for elderly or frail patients. A systematic review of hypofractionated radiotherapy (RT) revealed high local control of 90% or higher, as well as a low probability of late toxicities (10%) [ 9 ]. However, there is little reported data regarding hypofractionated RT in elderly or frail patients with meningioma.…”
Section: Introductionmentioning
confidence: 99%
“…In a large retrospective series of 168 patients receiving CyberKnife-based hypofractionated SRT for SBMs, Marchetti et al [ 111 ] showed a local control rate of 95% at 5 years with a toxicity rate of 3.7%, and similar results have been observed in a few other studies using either CyberKnife or LINAC technologies. In a systematic review on the clinical outcomes of hypofractionated SRT for intracranial meningiomas including 630 patients reported in fourteen studies published between 2004 and 2016, Nguyen et al [ 112 ] reported a crude control of 90–100% with median late toxicity rates of about 10%.…”
Section: Radiation Therapymentioning
confidence: 99%